The influence of the inquiry learning model on dribbling learning outcomes in basket ball - Saefudin, Saefudin; Nurbait, Syifa; Widiyastuti, Suciati Rahayu (Jurnal Ilmu Keolahragaan, 2022)
This study aims to determine the influence of the inquiry learning model on the learning outcomes of dribbling skills in basketball games in grade VIII students at MTs. Nurul Falah Durajaya. The underlying problem is the low mastery of students' basic dribbling techniques which is characterized by a lack of ball control and movement coordination during learning. The research method used is quantitative with a one group pretest-posttest design. The research sample amounted to 33 students who were randomly selected from a population of 132 grade VIII students. The research instrument was in the form of a dribbling skill test with a soccer dribble test and a practice assessment sheet. Data were analyzed using normality tests, homogeneity tests, and hypothesis tests (t tests). The results of the analysis showed an increase in dribbling learning outcomes after the application of the inquiry learning model. The average posttest score.